Discharging Firearms & Carrying Concealed Weapons, Ch. 28, § 5, in Revised Ordinances of the City of Omaha (1872) - (:unkn) unknown (General Publisher, 1872)
If any person shall unnecessarily discharge any fire-arms, or shoot off any fire-crackers, or other fire-works, or shall light or throw any fire-ball or crackers, in said city [i.e., Omaha], without permission of the Mayor, such person so doing, shall, on conviction thereof, be fined in any sum not exceeding twenty dollars.
--
Keywords: DISCHARGE